Implementasi Peraturan Perundang-Undangan Tentang Diversi Tindak Pidana Anak di Polresta Yogyakarta - Eva Albatun Nabilah (UIN Sunan Kalijaga Yogyakarta, 2018)
processes to processes outside criminal justice. Diversion was only implemented in 2014, two years after the enactment of Law No. 11 of 2012 concerning the Child Criminal Justice System. The purpose of implementing diversion is to create restorative justice in the juvenile justice system. Restorative justice is believed to be able to overcome the high rate of child crime in Indonesia. In fact, in Yogyakarta, even though diversion has been implemented, the number of children committing crimes is still high. Based on this, the authors are interested in examining two things, namely examining the related implementation of diversion in Yogyakarta Police towards all criminal offenses that meet the requirements of attempted diversion and to see its implementation in terms of the objectives of the Child Criminal Justice System.This research uses a jurisdictional-empirical approach by looking at the suitability between the Law and the reality at the Yogyakarta Police. This research is descriptive analysis by conducting interviews and observations as data collection techniques.The results of this study, the authors conclude that not all child crimes in Yogyakarta Police are attempted diversion according to the mandate of the Child Criminal Justice System Act, even though the criminal offense of the child has fulfilled the requirements for diversion. This is because in practice, in addition to using diversion solutions, Yogyakarta Police also has another solution called